Drawn and quartered - Cioran, Emile Michel, 1911-1995; Howard, Richard, 1929-2022; Thacker, Eugene (New York : Arcade Publishing, 2012)
Cioran overstelpt ons in dit boek opnieuw met een hele lading aforismen.
The two truths -- The addict of memoirs -- After history -- Urgency of the worst -- Stabs at bewilderment.
Originally published by Editions Gallimard, Paris, France, under the title Ecartelement.
Previously published in English: New York : Seaver Books, 1983.
Includes bibliographical references.
Keywords: Philosophy, Modern -- 20th century; Truth